2011
DOI: 10.1152/ajpendo.00670.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia in the elderly involves increased incorporation of ingested fat in plasma free fatty acids and small (Sf20–400) triglyceride-rich lipoproteins

Abstract: In the elderly, the rise in postprandial plasma triglyceride (TG) concentrations is increased, contributing to their increased risk of cardiovascular disease. We sought to determine the incorporation of ingested fat (whipping cream enriched with [1,1,1-13 C]triolein) into plasma lipids during the postprandial period in six healthy elderly (67 Ϯ 1 yr old) and six healthy young (23 Ϯ 2 yr old) subjects. Blood and expired air samples were taken before and at 2-h intervals during the 8-h postprandial period. As ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 26 publications
2
37
0
Order By: Relevance
“…Age Postprandial hypertriglyceridemia is significantly higher in older compared with younger subjects 27,28 . However, the increasing prevalence of pediatric overweight and obesity 29 and the notion that obesity in childhood predicts cardiovascular disease, led the focus of attention to preventive early approaches.…”
Section: Physiological Factorsmentioning
confidence: 99%
“…Age Postprandial hypertriglyceridemia is significantly higher in older compared with younger subjects 27,28 . However, the increasing prevalence of pediatric overweight and obesity 29 and the notion that obesity in childhood predicts cardiovascular disease, led the focus of attention to preventive early approaches.…”
Section: Physiological Factorsmentioning
confidence: 99%
“…We have shown that after ingestion of a moderate amount of dietary fat (0.7 g · kg body weight 21 ), older men respond with an apparently greater increase in the postprandial plasma FFA concentrations compared with younger men, an effect observed together with greater postprandial spillover of dietary lipid (10). We hypothesized that the postprandial spillover of dietary lipid induced by the ingestion of a moderate amount of dietary fat in older men can be attenuated by lowering the amount of ingested fat.…”
Section: Introductionmentioning
confidence: 88%
“…Dietary fat was provided in the form of heavy whipping cream: low (LF) and moderate (MF) fat ingestions corresponding to 0.4 and 0.7 g · kg body weight 21 , respectively. Some of the data related to the ingestion of the moderate amount of dietary fat were previously reported (10). Depending on the participantÕs weight, 33-39 g of fat was ingested in the LF trial and 54-65 g was ingested in the MF trial.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations